Learning from Nature: Lessons Distilled by Focused Awareness - Palafox, Juan Amor F. (Philippine Journal of Labor and Industrial Relations, 2021)
One of the better-known techniques of drawing lessons is the use of metaphors in learning experiences. And what better way to draw metaphors in organizational processes than to bring organizational members to the greatest resource of metaphor - that is nature. This paper illustrates how the learning facilitator uses metaphors to draw lessons from participants communing or interacting with nature in the mildest to the most extreme form: walking, trekking, dipping, swimming, boating, climbing, jumping, spelunking, diving or simply being there sensing Mother Nature go through its own course. Lessons that could be synthesized are bountiful: from individual accountability to motivation and personal effectiveness; from maintaining balance to dealing with change; leadership to membership roles; communication to power dynamics; teamwork to coordination and organizational effectiveness. Only the skills of the facilitator may limit his/her ability to maximize the learning opportunities posed by nature, as leaning from it is as vast and limitless - like nature itself.